Determinantes e conseqüências da insegurança alimentar no Amazonas: a influência dos ecossistemas - Alencar, Fernando Hélio; Yuyama, Lucia Kiyoko Ozaki; Varejão, Maria de Jesus Coutinho; Marinho, Helyde Albuquerque (Acta Amazonica, 2007)
In this review were investigated the principal determinants of the epidemic transition, nutritional and of the pattern of physical activity lived on by Brazilians in the last three decades. It is verified in these researches the systematic exclusion of the rural area from North region of the new national epidemic picture, currently characterized by the decline of the infantile malnutrition and concomitant rise of the obesity, beyond the lack of scientific investigation to be in reference the health, nutrition and survival conditions of the practically all the populations of North region states. Specifically for Amazonas state lesser stature is referred among the Brazilian children that become evident to exposition nutritional needs at long term. The same way, the evolutionary analysis of the regional researches characterizes the persistence of a serious picture of alimentary insecurity. However, it is known that the Amazonia holds a great diversity in fishes and fruits, what should represent an abundant offer and to make use of protein of the highest biological quality, calories, vitamins, minerals, and like this, to make possible an appropriate pattern of health, nutrition and life quality for its population. The social and economical reality, as well as the picture of precariousness of the health and nutritional of the region contradicts with its abundance in natural resources. For the understanding of this obvious paradox the components of the Amazon Bioma were investigated with relation to the: heterogeneity, complexity, fragility, interactivity and their relations with the alimentary potential of the region, as well as its influence ability in the determination of the binomial health versus nutrition for the inhabitants of their several ecosystems.
Alimentary insecurity determinants and consequences at Amazonas: ecosystems influences
Keywords: Malnutrition; Alimentary Insecurity; Amazonian Ecosystems; Alimentary Potential; Brazilian Amazon; Desnutrição; Insegurança Alimentar; Ecossistemas Amazônicos; Potencial Alimentar; Amazônia-brasil